Weather Contracts: Capturing a sense of weather for place-based adaptation to climate change. (July 2020) - Butts, Deborah; Adams, Helen
Abstract: Place attachment, the emotional bonds that people form to significant places, influences adaptation to climate change. Within this context, weather is garnering greater attention for its dynamic, mediating role, yet its political and cultural significance remains under-researched. Here we draw on Serres and McCarren's (1992) idea of the Natural Contract and Vannini et al. 's (2012) contributions on weathering to integrate contractarianism with a deep account of people's relationship with weather in place. We analyse attitudes and adaptation to climate change in communities of the geographically-remote and climate-vulnerable Outer Hebrides in Scotland, using video-elicitation to generate data on significant places. Our results show that changing, difficult and unpredictable weather binds people to place and influences how they think about themselves, their place and adaptation in dynamic ways. Through this connection, we demonstrate that people knowingly enter into what we term Weather Contracts and that accepting the volatility of the weather allows people to react positively to changes brought with climate. Finally, we show that the common ideology of a community living with weather generates wider discourses around independence and resisting modernisation that we term a weathered ideology . Thus, climate change is not always a destabilising force. For those who are accustomed to changing weather it can be a dimension of place around which people can organise. Uncertainty and anxiety about the future of the climate is caused more by a lack of control over adaptation processes than by a fear of unknown weather. This has implications for people living at the margins across the globe, where unpredictable weather is a part of local identities, but influence on adaptation policy making is low.